2022
DOI: 10.3201/eid2813.220743
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging HIV Program and Civil Society to Accelerate COVID-19 Vaccine Uptake, Zambia

Abstract: To accelerate COVID-19 vaccination delivery, Zambia integrated COVID-19 vaccination into HIV treatment centers and used World AIDS Day 2021 to launch a national vaccination campaign. This campaign was associated with significantly increased vaccinations, demonstrating that HIV programs can be leveraged to increase COVID-19 vaccine uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In Zambia, the MOH targeted PLHIV for COVID-19 vaccinations given their elevated risk of severe disease and substantial investments and achievements in HIV care in the country. 46 In our study, we assessed vaccine hesitancy among HIV-infected pregnant women and found a high degree of COVID-19 vaccine uptake among HIV-infected pregnant women as compared to those who were not infected with HIV. These results suggest high levels of vaccine acceptability and accessibility among pregnant women living with HIV.…”
Section: Vaccine Uptake Over Timementioning
confidence: 88%
“…In Zambia, the MOH targeted PLHIV for COVID-19 vaccinations given their elevated risk of severe disease and substantial investments and achievements in HIV care in the country. 46 In our study, we assessed vaccine hesitancy among HIV-infected pregnant women and found a high degree of COVID-19 vaccine uptake among HIV-infected pregnant women as compared to those who were not infected with HIV. These results suggest high levels of vaccine acceptability and accessibility among pregnant women living with HIV.…”
Section: Vaccine Uptake Over Timementioning
confidence: 88%
“…Considering ongoing need for COVID-19 vaccine delivery in Zambia, where possible, COVID-19 vaccination could be integrated into other healthcare services to improve efficiency in under-resourced health systems like in Zambia. 29 Examples of existing platforms include vaccination in HIV care clinics supported by the US President’s Emergency Plan for AIDS Relief, routine antenatal care services, for inpatients prior to discharge from the hospital, or into Expanded Programme on Immunisation programmes such as mass measles or polio vaccination campaigns. New SARS-CoV-2 variants are predicted to emerge, 27 30 and thus having an ongoing ability to conduct VE studies in Zambia will be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences from past rubella vaccination programs ( 28 ), yellow fever and polio immunization campaigns for COVID-19 vaccine deployment and safety monitoring in Ghana ( 29 ), and the effectiveness of inactivated whole-virus COVID-19 vaccine among healthcare personnel in Peru ( 30 ) can also inform future responses. Zambia integrated COVID-19 vaccination at HIV treatment centers and combined activities planned for 2021 World AIDS Day to help increase vaccination outreach ( 31 ). Kimani et al assessed IPC strategies and health facility readiness for responding to COVID-19 in Kenya, providing important data to guide IPC improvements ( 32 ).…”
Section: Clinical and Health Services Delivery And Impactmentioning
confidence: 99%